Pengaruh Green Brand Knowledge Dan Attitude Toward Green Brand Terhadap Green Purchase Intention Di Restoran Kehidupan Tidak Pernah Berakhir Kota Bandung Tahun 2019 - Yolanda Agustiningsih; Rennyta Yusiana (eProceedings of Applied Science, 2019)
At present the existence of environmental damage issues is a concern of all people in the world. This is due to the increasing number of causes of environmental damage, moreover the consequences of environmental damage are beginning to be felt for everyone, starting from the many natural disasters that have occurred lately. One reason is the occurrence of global warming. With the occurrence of global warming, people are aware that they are better at protecting the environment, one of which is by starting to consume green products or green products, namely products that start from the manufacturing process to decomposition do not have a bad effect on the environment. To make people aware of the benefits of green products, knowledge of the brand of the product is needed. The purpose of this study was to determine the effect of Green Brand Knowledge and Attitude Toward Green Brand on Green Purchase Intention at Kehidupan Tidak Pernah Berakhir Restaurants. Data collection is done by distributing questionnaires to 400 people in Bandung City also interviews with the company’s management. The research method used in this study is a mixed method, and the data analysis technique used is multiple linear regression. The result of this study is that Green Brand Knowledge has partial influence on Green Purchase Intention with significance value of 0.001, for Attitude Toward Green Brand has a partial influence on Green Purchase Intention with significance value of 0.000 and the result of both variables, and for Green Brand Knowledge and Attitude Toward Green Brand effect simultaneously (together) on Green Purchase Intention with the value of Significance of 0.000. Then it can be interpreted that the statements on hypotheses 1, statements on hypotheses 2 and statements on hypotheses 3 are accepted. Keyword: Green Marketing, Green Brand Knowledge, Attitude Toward Green Brand, Green Purchase Intention, Multiple Linear Regression